Examining the Relationship between Psychological Capital and Entrepreneurial Intention: An Exploratory Study (2015)
The aim of this study is determine if Entrepreneurial Intention is related to Psychological Capital in business students. Self-efficacy, Hope, Optimism and Resiliency, which are all dimensions of psychological capital, were assessed with the General Self-Efficacy Scale (GSE), the Hope Scale (HS), the Life Orientation Test Revised (LOT-R) and the Resilience Scale (RS), respectively. The Entrepreneurial Intention was assessed through five statements. According to the results, Entrepreneurial Intention is related to all dimensions of Psychological Capital, mainly with Self-efficacy and Resilience. Psychological Capital as an integrated construct was related to Entrepreneurial Intention as a whole. These findings provide additional evidence about the importance to study Psychological capital as an integrated construct instead of studying its dimensions separately, even more so when studied in relation to Entrepreneurial Intention. In spite of the advances in the knowledge about the individual differences related to entrepreneurial intentions, it is necessary to continue studying this phenomenon, considering that the results are still scarce and inconclusive.